Synthetic vascular access graft in hemodialysis patients: patency rate and complications - Salimi J (Tehran University Medical Journal, 2007)
Background: Dialysis access procedures and complications are important causes of morbidity and hospitalization for chronic hemodialysis patients. Ideally, any patient undergoing hemodialysis should receive an autogenous fistula that can be accessed throughout the patient's life. In patients with primarily unsuitable or secondarily surgically-exhausted veins, a prosthetic graft can be performed. Several recently published studies report the outcome of prosthetic grafts. The conclusions of these studies differ dramatically. The aim of this prospective study was to determine the patency, infection and thrombosis rates using Poly-tetrafluoroethylene (PTFE) in grafts for vascular access in hemodialysis patients. Methods: During this three-year prospective study, 84 patients underwent placement of vascular access graft at the Vascular Surgery Department of Sina Trauma and Surgery Research Center in Tehran. Demographics, complications, and subsequent treatment were recorded. Primary patency rates were estimated using the Kaplan-Meier method. Logrank tests were used to evaluate the statistical differences in survival distribution. Results: The mean patient age was 55 years (±12 years). Hypertension, diabetes and smoking were considered to be risk factors for atherosclerosis in 45, 26 and 19 cases, respectively. The patients were followed up for at least 24 months. The primary patency rates were 78%, 63.3% and 54.9% at 6, 12 and 18 months, respectively. There were 39 (46.4%) access failures, which were related to infection in five cases (6%), thrombosis in 30 cases (35.7%) and bleeding in two cases (2.4%). The patency rate in patients without hypertension and with hypertension were 62.2% and 29.7%, respectively (P<0.03). Patency rates for upper extremity and lower extremity grafts were 60% and 26%, respectively (P<0.05). Conclusion: A PTFE vascular graft seems to be an appropriate vascular access and is a promising alternative when upper extremity arteriovenous fistulas cannot be constructed. Additionally, good care and educating patients can further decrease the rate of complication and morbidity, thereby resulting in a better patency rate.Salimi J. *1 Rostamnejad M.1"nMeisami A.P.2"n1- Sina Trauma & Surgery"nResearch Center"n2- Department of Social Medicine"nTehran University of Medical"nSciences